The precise NLP model - Schmidt, Martin; Steinbach, Marc C.; Willert, Bernhard M. (Evaluating Gas Network Capacities, 2015)
In this chapter we describe a highly detailed nonlinear program (NLP) of gas networks for the case of fixed discrete decisions. By including nonlinear physics and a detailed description of the technical network devices, a level of accuracy is reached that is comparable to current commercial simulation software. Our NLP model is used to validate the solutions of the previously described models. A successful validation provides a solution of the underlying mixed-integer nonlinear program (MINLP).